Adsorption Study of Main Gas Products from Water Radiolysis on 4A Zeolite by Numerical Simulations. (2nd January 2021) - Randrianandraina, Joharimanitra; Grivet, Manuel; Ramseyer, Christophe; Groetz, Jean-Emmanuel; Cardey, Bruno; Torrealba Anzola, Freddy; Ducret, Didier; Chambelland, Caroline
Abstract: This work is motivated by the results obtained during a study on the tritiated water adsorbed in zeolite [L. Frances et al., J. Phys. Chem. C, 119, 28462 (2015)]. The decomposition of water by radiolysis leads to the production of dioxygen and dihydrogen as main stable products. By studying the evolution of their quantities of matter, one can note an increase in a first stage, followed by a decrease after a few hundred days of storage until complete disappearance. This interesting process depends on the water loading ratios, expressed in mass percentage, lying between 4%, and 19%; such a phenomenon is not observed in saturated zeolite. Our goal is to determine, through numerical simulations, how this disappearance, which is associated with the recombination of the radiolysis products, occurs by making a microscopic study on the adsorption of H2 O, H2, and O2 molecules on 4A zeolite (Z4A). Computational physics is useful to understand the effects of molecule adsorption on its structure and also to closely examine the molecule-zeolite and molecule-molecule interactions. Indeed, different simulation methods are used from static to dynamic studies employing both quantum and classical tools with the periodical structure of Z4A. To summarize, the adsorption of molecules from the radiolysis of water are studied according to different points of view (quantum and classical) using various numerical simulation tools, such as density functional theory for ab initio structural optimization and energy calculation, Monte Carlo to study the distribution of the adsorbed molecules in the zeolite, and molecular dynamics to follow the evolution of the system (molecule + zeolite) over time depending on the temperature, in order to extract as much information as possible (structurally, statistically, energy, electronically) to understand the main problematic of this work: How do stable molecules issued from radiolysis recombine in Z4A?